2023
DOI: 10.5194/egusphere-egu23-1675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Retrogressive Thaw Slumps Using Satellite Data With Deep Learning

Abstract: <p>Retrogressive thaw slumps (RTS) are thermokarst features in ice-rich hillslope permafrost terrain and can cause dynamic changes to the landscape. Their occurrence in the Arctic has become increasingly frequent. RTS can significantly impact permafrost stability and generate substantial carbon emissions. Understanding the spatial distribution of RTS is critical to understanding and modelling global warming factors from permafrost thaw. Mapping RTS using conventional Earth observation approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies reported maximum IoU values of 0.58 (Nitze et al, 2021), and 0.74 (Yang et al, 2023) or F1 values of 0.73 (Nitze et al, 2021), 0.75-0.85 (Witharana et al, 2022) and 0.85 (Huang et al, 2020). These previous studies typically used calibration and validation data from one or a few participants, thus the maximum IoUs reported reflect the degree to which DL frameworks can mimic the participants' ontological understandings and delineation tendencies.…”
Section: Comparison To Published Accuraciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported maximum IoU values of 0.58 (Nitze et al, 2021), and 0.74 (Yang et al, 2023) or F1 values of 0.73 (Nitze et al, 2021), 0.75-0.85 (Witharana et al, 2022) and 0.85 (Huang et al, 2020). These previous studies typically used calibration and validation data from one or a few participants, thus the maximum IoUs reported reflect the degree to which DL frameworks can mimic the participants' ontological understandings and delineation tendencies.…”
Section: Comparison To Published Accuraciesmentioning
confidence: 99%
“…(Nitze et al, 2021). However, they all achieved accuracy metrics using IoU (intersection over Union), which ranged from low to very good agreement: 0.15-0.58 (Nitze et al, 2021), 0.71-0.74 (Yang et al, 2023) or F1 of 0.25-0.73 (Nitze et al, 2021), 0.85 (Huang et al, 2020) and 0.75-0.85 (Witharana et al, 2022). As these values are relative to validation data based on self-created hand-drawn labels, and not independent benchmark datasets, accuracy metrics are difficult to compare across methods and geographical regions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation